The Effects of Organizational Climate and Transformative Leadership on Islamic Boarding School Teacher Performance - Prasetyo, Muhammad Anggung Manumanoso (Graduate Program Magister Manajemen Pendidikan, 2021)
This empirical study observed the effects of organizational climate and transformative leadership on teacher’s performance of Sholahuddin Gayo Lues Islamic Boarding School. This study used quantitative approach using survey method. The data collection technique used questionnaires with likert scale. These research samples are all population so it can be said to be the population research. Descriptive statistic and regression analysis were used to describe variation in organizational climate transformative leadership and teacher performance. Through statistic hypothesis calculation, results of the research show that organizational climate and transformative leadership have great effects on the teacher performance.